PENGARUH KOMPETENSI, INDEPENDENSI DAN FAKTOR-FAKTOR DALAM DIRI AUDITOR LAINNYA TERHADAP KUALITAS AUDIT - OKLIVIA OKLIVIA; AAN MARLINAH (Jurnal Bisnis dan Akuntansi, 2014)
The purpose of this research is to analyze how far the competency, independency, job experience, objectivity, integrity and time budget pressure influence on audit quality. This research conducted by using survey method with questionnaires to public accountant auditors in Jakarta. This research is using Purposive sampling method and the data is analyzed by using multiple regression. The result of this research shows that job experience, objectivity and integrity had significant influence on audit quality. However, competency, independency and time budget pressure had no significant influence on audit quality